QT Interval Prolongation Associated with Amiodarone Use in Cipto Mangunkusumo Hospital, Jakarta - Nafrialdi Nafrialdi; Theresia G Kurniawan; Arini Setiawati; Lukman H. Makmun (Acta Medica Indonesiana, 2014)
Aim: to evaluate the incidence of QTc interval prolongation associated with the use of amiodarone, as well as factors that influence its occurrence. Methods: this was a descriptive retrospective study conducted from November 2010 until December 2011 using medical record of patients at ICCU Cipto Mangunkusumo Hospital from 2004-2011. Four groups of patients were included: (1) patients receiving amiodarone and other drugs causing which can cause QTc prolongation, (2) patients receiving amiodarone and other drug not causing QTc prolongation, (3) patients receiving drugs which can cause causing QTc prolongation, (4) patients not receiving amiodarone, nor other drugs which can cause causing QTc prolongation (served as control group). Difference of QTc interval within the same group was analyzed with paired t-test or Wilcoxon matched-pairs test. Between groups comparison were performed with Kruskal Wallis test. The influence of other factors (sex, age, heart failure, liver disorder, electrolyte imbalance) on QTc prolongation was analyzed using multiple regression. Results: QTc interval prolongation in groups 1, 2, and 3 were respectively 65.5%, 63.3%, 56.6%, which were significantly different from control group (24.4%); Hypernatremia and hypertension were revealed as significant risk factor for QTc prolongation. Mortality occurred in 3, 4, and 4 patients in group 1, 2, and 3 respectively, and none in group 4. Conclusion: QTc interval prolongation occurred in association with amiodarone and other drugs known to prolong QTc interval. Hypernatremia and hypertension were shown as significant influencing factor of QTc interval prolongation.